Pendampingan Sistem Informasi Desa Dalam Meningkatkan Pelayanan Masyarakat di Desa Sambisirah Wonorejo Pasuruan - Lailatuzzahro Al-Akhda Aulia (Jurnal Soeropati, 2021)
Technological developments that have entered the 4.0 industrial revolution present their own challenges for village governments. On the other hand, the condition of the COVID-19 pandemic, which has not ended more or less, has hampered all forms of activity in society. as happened in Sambisirah Village, Wonorejo District, Pasuruan Regency. In a pandemic, and the implementation of PPKM (Implementation of Community Activity Restrictions) certainly has an impact on people who want to complete general administration. This service activity is carried out with the aim of improving the quality of service and information through the creation of a website. This service activity uses a Community Based-Participatory Research (CBPR) approach, with the Focus Group Discussion (FGD) method, interviews, and simulations. The implementation of this activity resulted in a Village website hosted with the url address pemdessambisirah.id. With this website, it is expected to improve the quality of service and information in Sambisirah Village.